MUTUAL COMMONALITIES IN THE WORKS OF ANTON PAVLOVICH CHEKHOV AND ABDULLA KAHKHOR (Conferencea, 2024)
This article discusses the influence of Anton Pavlovich Chekhov, one of the Russian literary figures, on the work of Abdulla Kahkhor, their skill in using words, the unique style of Abdulla Kahkhor and Anton Pavlovich Chekhov, and the storytelling of Abdulla Kahkhor.